Amending the algorithm of aerosol–radiation interactions in WRF-Chem (v4.4) - J. Feng; C. Zhao; C. Zhao; C. Zhao; C. Zhao; C. Zhao; C. Zhao; Q. Du; Z. Yang; C. Jin (Geoscientific Model Development)
WRF-Chem (Weather Research and Forecasting model coupled with Chemistry) is widely used to assess regional aerosol radiative feedback. However, in the current version, aerosol optical properties are only calculated in four shortwave bands, while only two of them are used to interpolate optical properties towards the 14 shortwave bands used in the Rapid Radiative Transfer Model for Global Climate Models (RRTMG) scheme. In this study, we use a “Resolved” algorithm to estimate aerosol radiative feedback in WRF-Chem, in which aerosol optical properties are calculated in all 14 shortwave bands. The impacts of changing this calculation algorithm are then evaluated. The simulation results of aerosol optical properties are quite different using the new Resolved algorithm, especially for dust aerosols. The alteration of aerosol optical properties results in considerably different aerosol radiative effects: the dust radiative forcing in the atmosphere simulated by the Resolved algorithm is about 2 times larger than the original “Interpolated” algorithm. The dust radiative forcing at the top of the atmosphere (TOA) simulated by the Interpolated algorithm is negative in the Sahara region, while the Resolved algorithm simulates positive forcing at TOA and can exceed 10 W m−2 in the Sahara, which is more consistent with previous studies. The modification also leads to changes in meteorological fields due to alterations in radiative feedback effects of aerosols. The near-surface temperature is changed due to the difference in the radiation budget at the bottom of the atmosphere (BOT) and the heating effects of aerosols at the surface. Furthermore, the amendment of the algorithm partially corrects the wind field and temperature simulation bias compared to the reanalysis data. The difference in planet boundary layer height can reach up to ∼100 m in China and ∼200 m in the Sahara, which also results in a greater surface haze. The results show that correcting the estimation algorithm of aerosol radiative effects is necessary in WRF-Chem.